Improving The Quality of Coconut Cream-Based Pasta Through The Presence of Sago Starch and Surfactants: Application As An Ingredient of Rendang Seasoning - Anggita Nugrahanto; Sutardi Sutardi; Umar Santoso (Indonesian Food and Nutrition Progress, 2021)
Coconut processed products (coconut cream) are widely used in the food field. However, various ways, such as addingKeywords:coconut cream, cream separator, cold method, sago starch, rendang seasoningstarch and surfactants, still need to be made to improve the stability of coconut cream. This study aimed to evaluate the addition of starch and surfactant on the stability of coconut cream and its use as an ingredient of rendang seasoning. The separation of coconut milk into coconut cream was conducted using the cold (4oC for ± 18 hours) and cream separator method. After that, Hydrophilic-Lipophilic Balance (HLB) 5 (1%) surfactant and sago starch (3% and 5%) were added to the coconut cream to produce a coconut cream paste, which was later used as an ingredient in the rendang seasoning. The quality parameters of coconut cream such as zeta potential, viscosity, free fatty acid content were evaluated in this study. The results showed that the cream separator method with 1% surfactant HLB 5 and 3% sago starch improved the coconut cream paste stability with a zeta potential of -30.5 mVand free fatty acid of 0.1%. This method was suitable for use as an ingredient of rendang seasoning indicated by a viscosity of 699.9 cPs, lightness of 32.51, and pH of 4.41. Therefore, the cream separator method could improve the coconut cream stability and be applied to rendang seasoning